2014
DOI: 10.9767/bcrec.9.2.6794.148-154
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Biginelli Condensation using Tungstate Sulfuric Acid: a Powerful and Reusable Catalyst for Selective Synthesis

Abstract: Tungstate sulfuric acid (TSA) has been prepared and used as a recyclable catalyst for the Biginelli synthesis of some biologically active quinazolinones/thiones under solvent-free conditions. This method has advantages such as the avoidance of organic solvents, high yield of pure products, short reaction times, and operational simplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Based on the observed results, the SAR study indicated that, compounds 4d and 4e substituted with a NO 2 group at the 2 and 4-position of the phenyl ring showed the lowest cytotoxic activities which could be attributed to the withdrawing effects on the phenyl ring. Moreover, the compounds substituted with 6, 8-dichloro have shown better activity than 6-chloro substituted compounds which could be due to the inductive effect on the heterocycle compounds( 21 32 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observed results, the SAR study indicated that, compounds 4d and 4e substituted with a NO 2 group at the 2 and 4-position of the phenyl ring showed the lowest cytotoxic activities which could be attributed to the withdrawing effects on the phenyl ring. Moreover, the compounds substituted with 6, 8-dichloro have shown better activity than 6-chloro substituted compounds which could be due to the inductive effect on the heterocycle compounds( 21 32 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of DNA gyrase in all bacteria except higher eukaryotes, makes it a drug target for antibacterial studies ( 4 5 ). Over the past decade, the quinazolin-4(3H)-one structural motifs containing azomethine (-C=N) functional group has become one of the main areas of interest due to possessing a wide spectrum of biological activities including antibacterial, antifungal, anticonvulsant, anti-inflammatory, antiviral, antihyperlipidemic, anti-tubercular, CNS depressant, anti-tumor, analgesic, antimalarial, and anti-cancer effects ( 6 7 ). Azomethine functional groups are formed when a primary amine reacts with a carbonyl compound ( 8 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme belongs to a superfamily of ATPases which is a known target for antibacterial agents since its blocking induces bacterial death ( 4 5 ). Quinazolines are a class of fused pyrimidine derivatives, which show a wide range of biological activities and used widely in the pharmaceutical industry, medicine and agriculture ( 6 7 8 9 10 11 ). Quinazolines act as an important backbone for a range of inhibitors of enzymes such as tyrosine kinase, thymidylate synthase and dihydrofolate reductase ( 12 13 14 ).…”
Section: Introductionmentioning
confidence: 99%